2001
DOI: 10.1038/sj.leu.2402188
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability in chromosome band 12p13: multiple breaks leading to complex rearrangements including cytogenetically undetectable sub-clones

Abstract: During fluorescence in situ hybridization (FISH) analysis of metaphase cells from 70 patients with lymphoid and myeloid hematologic malignancies and chromosomal rearrangements involving band 12p13, we identified nine patients (four with lymphoid malignancies, four with myeloid malignancies and one with biphenotypic leukemia) who showed more complicated rearrangements than we had expected from conventional cytogenetic study. In six patients, multiple breaks occurred in small segments of 12p with subsequent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Chromosome 12 is also frequently involved in translocations, and the short arm is often deleted. 35 We also observed frequent loss of chromosome 18q, which is in agreement with previous reports in primary colorectal tumors. 11,36 HCT116, DLD-1 and LoVo cell lines are classified as MSI tumors since they show few chromosomal abnormalities and MSI.…”
Section: Discussionsupporting
confidence: 93%
“…Chromosome 12 is also frequently involved in translocations, and the short arm is often deleted. 35 We also observed frequent loss of chromosome 18q, which is in agreement with previous reports in primary colorectal tumors. 11,36 HCT116, DLD-1 and LoVo cell lines are classified as MSI tumors since they show few chromosomal abnormalities and MSI.…”
Section: Discussionsupporting
confidence: 93%
“…Cases with unbalanced 12p translocations appear to be closely associated with complex karyotypes, and in most cases the breakpoints have been reported to be outside ETV6, as was true for all our patients [14,15]. SKY is an important tool to characterize the aberrations in these cases [23].…”
Section: Resultssupporting
confidence: 62%
“…These deletions in some cases are different from the region reported in ETV6-CBFA2 positive ALL [12]. Unbalanced translocations involving ETV6 have rarely been described [13,14], and cases with breakpoints outside ETV6 appear to be strongly associated with complex karyotypes [14,15].…”
Section: Introductionmentioning
confidence: 85%
“…Material from 7q was also inserted into the long arm of this der (9). The second copy of chromosome 12 had an interstitial deletion including part of ETV6.…”
Section: Case 5944mentioning
confidence: 99%
“…2 Subsequently it has been shown that ETV6 is involved in a significant number of cases with visible cytogenetic abnormalities of 12p or loss of heterozygosity (LOH) in that region. [3][4][5][6][7][8][9] There is some evidence that the gene is more often involved when the 12p rearrangements are balanced rather than unbalanced, the latter often being associated with a complex karyotype. 10,11 The inherent instability of the ETV6 gene has been demonstrated in several different studies by the use of cosmid probes to its individual exons.…”
Section: Introductionmentioning
confidence: 99%